Pandemic Risk - Jonas, Olga B. (World Bank, Washington, DC, 2013)
This study examines pandemic risk, what it means for development, and how management could be improved, both in countries and internationally. Widely held beliefs—the inevitability of pandemics, which makes them not worth worrying about, health sector exclusive management of the risks, and the nondevelopmental nature of pandemic risk—lead to underestimation, scant preparedness, and inadequate prevention. Examining the reasons why these myths persist could help governments and international organizations improve management of the risks associated with pandemics, since reduction of pandemic risk remains a public service only governments, through their coordinated actions, can provide, and delivery of this service can benefit from systematic application of ‘science of delivery,’ notably by using One Health approaches for early effective control of contagion. Preparedness for pandemics remains low everywhere, but especially in developing countries, with potentially high-cost impacts on health, economies, and society. Low-cost, whole-of-society planning for responses can mitigate these impacts.